Financial Development, Economic Growth and Income Inequality in Central Eastern European Transition Economies: Evidence from the Toda-Yamamoto Panel Causality Test - Sotiropoulou, Theodora (Ekonomika, 2025)
This study rigorously examines the causality between banking development, economic growth, and income inequality using annual panel data for 13 Central Eastern European transition economies from 2000 to 2020. The Granger non-causality test of heterogeneous panels based on the Toda and Yamamoto approach is employed for the empirical analysis. The main findings establish a trivariate causal relationship between financial development, economic growth, and inequality. In particular, the banking development measured by private credit provided by the financial sector and liquid liabilities Granger causes economic growth, and economic growth Granger causes income inequality. Based on the results, policy implications in European transition economies should focus primarily on expansion and banking system reforms so that to improve financial services, leading to enhanced economic growth. The boosted economic activity could ameliorate income inequality and improve social welfare.
Keywords: Economic growth; Financial development; Inequality; trivariate panel causality; CEE countries